IMPLEMENTASI KONSEP “ZERO WASTE PRODUCTION MANAGEMENT” BIDANG PERTANIAN: PENGOMPOSAN JERAMI PADI ORGANIK DAN PEMANFAATANNYA - Arief Sabdo Yuwono (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThe huge amount of rice straw as by-product of rice production system and the potential useof it as raw material of compost production for organic rice cultivation was the backgroundof this research. Here, rice straw was concerned as raw material to produce compost insteadof as waste from rice cultivation. The objectives of the research were to implement theconcept of “Zero waste production management” in agriculture by composting rice strawgenerated from an experimental field; to develop an input-output (waste-compost) massbalance in organic rice cultivation system; and, to apply the resulted compost on the ricefield. Materials necessary for the research covered an experimental organic rice field locatedin Bogor Municipality, rice seed, rice straw and goat manure. The rice field obtained organicfertilizer merely from compost without any synthetic fertilizer. The produced rice straw andgoat manure were composted by natural static pile method. The result of the researchindicated that waste-compost mass balance based on one hectare rice field showed that theproduced straw was ± 14.1 ton and the resulted compost was around 11.3 ton. It is merely 7ton from the produced compost necessary to apply in one hectare of rice field according toThe Ministry of Agriculture recommendation. It can be concluded that if the entire ricestraw produced from one hectare of rice field was composted, then the rice field could becompost self sufficient and even the rest of 4.3 ton could be utilized for other purposes.